INOVASI GICO (GINGER COFFEE) MOCKTAIL DENGAN METODE CLARIFIED - Anggraeni, Puput Dewi (Politeknik Harapan Bersama, 2024)
The development of cafes is currently increasing rapidly, the cafe itself can be used as a place to hang out from teenagers to parents, the coffee shop and mocktail business is growing rapidly in many cities in Indonesia. In this research, the drink that will be made is GICO (Ginger coffee) mocktail with the clarified method, Ginger coffee is currently favored by many people from teenagers to the elderly, Ginger coffee made from coffee and ginger with a filtering process. The purpose of this study was to find out how to make the Ginger coffee mocktail experiment. This study was experimental research. The method used was the clarified method to change the particles and color of the drink. This study used organoleptic test analysis and then processed using SPSS (Statistical Product and Service Solution) tools. The results in this study indicated that the average value of taste 4.02, texture 4.02, color 3.89, aroma 3.91. It can be concluded that the GICO (Ginger coffee) mocktail innovation with the clarified method declared as accepted.